Molecular Characterization of Carbapenem-Resistant Klebsiella Pneumoniae: Detection of Blandm and Other Resistance Genes by PCR - Dr. S. Rajeswari; Dr. R.Vasanthi; Dr. M. Umamaheswari, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: The global rise of carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant public health challenge. Early molecular identification of carbapenemase genes is critical for guiding treatment and infection control. Aim: This study aimed to characterize carbapenem resistance in phenotypically confirmed K. pneumoniae isolates by detecting major carbapenemase genes (blaKPC, blaNDM, blaOXA-48, blaIMP, and blaVIM) using multiplex PCR. Methods: Twenty-six meropenem-resistant K. pneumoniae isolates, selected from 196 clinical samples at a tertiary care hospital, underwent genomic DNA extraction and multiplex PCR amplification targeting five carbapenemase genes. PCR products were analyzed via agarose gel electrophoresis. Results: All 26 isolates (100%) harbored the blaNDM gene, while none tested positive for blaKPC, blaOXA-48, blaIMP, or blaVIM. The presence of a 621 bp amplicon confirmed blaNDM gene carriage. Conclusion: The exclusive presence of blaNDM indicates its predominant role in carbapenem resistance in the region studied. Molecular diagnostics are indispensable for accurate detection and epidemiological surveillance of multidrug-resistant organisms.